Periodontal Epidemiology - Bangalore Balaram, Santosh; Galgali, Sushma Ravindra; Rajendra Santosh, Arvind Babu (European Dental Research and Biomaterials Journal, 2020)
The increased requirement on the information about nature, etiology, and pathogenesis of periodontal disease has demanded wide areas of research in periodontics. The growth observed in research conducted in periodontology had been observed in both basic and clinical research areas. Despite recent advances in periodontal research, many issues remain unresolved. The aim of this review article is focused on few important problems faced in periodontal research related to epidemiology, etiology, and pathogenesis of periodontal disease.
Keywords: periodontal research; epidemiology; gingivitis; periodontitis; therapy